The right to be forgotten : a Canadian and comparative perspective - Privacy Revolution (Conference) (2018 : McGill University Centre for Intellectual Property Policy); Cofone, Ignacio N., 1987- (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Exploring the evolution of the right to be forgotten, its challenges, and impacts on privacy, reputation, and online expression, this book lays out the current state of the law on the right to be forgotten in Canada and in the international context while addressing the broader theoretical tensions at the core of the right to be forgotten. The essays contemplate questions such as: How does the right to be forgotten fit into existing legal frameworks? How can Canadian courts and policy-makers reconcile rights to privacy and rights to access publicly available information? Should search engines be regulated purely as commercial actors? What is the right's impact on free speech and freedom of the press? Together, these essays will address the questions that legal actors and policy-makers must consider as they move forward in shaping this new right through legislation, regulations, and jurisprudence. They will address both the difficulties in introducing the right and the long-term effects it could have on the protection of online (and offline) reputation and speech. While the question of implementing the right to be forgotten in Canada has been put forward by the Privacy Commissioner, Canada is in need of academic literature on the matter, a need that, with this book, we intend to remedy. The questions put forward in this book will thus advance the legal debate in Canada and provide a rich case study for the international legal community"--
Online Harms and the Right to be Forgotten / Ignacio N. Cofone -- Lost in Translation : Transposing the Right to be Forgotten from Different Legal Systems / Jennifer Stoddart -- A Little Knowledge is a Dangerous Thing? : Information Asymmetries and the Right to Be Forgotten / Teresa Scassa -- Reconciling Privacy and Expression Rights by Regulating Profile Compilation Services / Andrea Slane -- Let's Not Dwell On The Past : The Right to be Forgotten As More Than a Romantic Revolution / Pierre-Luc Déziel -- The Right to be Forgotten in Peace Processes / Ignacio N. Cofone and Catalina Turriago Betancourt.
OCLC-licensed vendor bibliographic record.
Keywords: Right to be forgotten -- Canada -- Congresses; Right to be forgotten -- Congresses; LAW / General